Ingen människa är en ö konstnärliga strandhugg i Stockhoms skärgård = No man is an island : artistic forays into the Stockholm archipelago - Nilsson, Bo 1954- (Artipelag, 2014)
The Stockholm archipelago has been the subject of many poems, songs and paintings. Today, however, the ideas of the archipelago increasingly appear as nostalgic tourist clichés, including the rather dubious artistic genre of "archipelago art". The exhibition No Man Is an Island enlists visual art from the end of 19th century until today, in an attempt to elaborate on the image of the archipelago with the point of departure in concepts such as class, gender and identity. The exhibition includes a number of artistic forays into various eras with the aim of reflecting the changes that have taken place in regard to the idea of the archipelago.
Keywords: Geschichte 1873-2014; Kunst; Malerei; Schäre -- Motiv; Schweden; Ausstellungskatalog -- Artipelag -- 22.05.2014-28.09.2014 -- Gustavsberg; Bildband